UTILIZATION OF EDUCATION MANAGEMENT INFORMATION SYSTEM (EMIS) AS AN ANTI-CORRUPTION EFFORT IN MADRASAS - Alfita Choirun Amalia; Luluk Wulandari; Evi Fatimatur Rusydiyah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to determine the use of the Education Management Information System (EMIS) within the Madrasah to implement anti-corruption education. This research belongs to the type of descriptive qualitative research by describing the facts or findings in the field. The data collection technique is done through interviews, observation methods, and documentation. The instrument used in this research is the instrument using a questionnaire. The results show that the use of the education management system (EMIS) as the implementation of anti-corruption education is quite effective because the distribution of Education Operational Costs (BOP) to madrasas no longer has to pass through various parties but is directly channeled through school accounts, so there are no more deductions in the distribution process. The use of EMIS is also inseparable from internal and external constraints. From the inner aspect, it includes human resources who do not understand EMIS operations. Meanwhile, external factors include the EMIS central server, which requires further improvement to comfort and convenience for madrasas.